RELATIONSHIP BETWEEN SCIENTIST’S REPRESENTATION IN THE DIGITAL SPACE AND DATA BASES OF PUBLICATIONS - Šarlauskienė, Lina (Knygotyra, 2016)
This article presents the results of analysing the possibilities of disseminating the results of scientific activity and deals with building a digital researcher identity, enhancing it by Web 2.0 tools and using academic library services. This research concludes the following tools for building up a researcher’s digital identity: publishing personal Curriculum Vitae and a list of scientific papers supported by indicators of science-metrics and the use of social networks and other Web 2.0 related tools; results of web search on a researcher’s scientific activity. The analysis of previous research works and case study were applied to determine the scope of application and the key problems arising from these tools in both Lithuania and on the international level. Alternative aspects of research dissemination are considered together with the traditional methods of research evaluation to achieve a better valorisation of scientific results and gain better recognition both on researcher’s personal and institutional levels. These aspects include researcher’s personal involvement into social scientific networks, active dissemination of daily and scientific information in the Web, institutional and national interest to the development of researcher databases, international cooperation for building, transferring and publicising lists of scientific papers.
Keywords: ...